(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2008)
Nutritional status of 327 boys and girls attending a high school in Dhaka City has been reported in this study. Weight for age (Wt/Age), height for age (Ht/Age) and weight for height (Wt/Ht) of the study participants were calculated and compared with the National Center for Health Statistics (NCHS) reference standards. Only 0.6% children were severely stunted and 4.3% were moderately stunted. In addition, 3.7% children were moderately wasted and 0.6% children were severely wasted. One girl was severely and 2.1% children were moderately underweight level. The overall nutritional status of the study samples was better than country situation and cannot be the similar to that of same age group of population of the country. Here, the children of the privileged class represent a typical group of population of the city. Key words: Nutritional value, School student, Weight per age and height. DOI: 10.3329.bjsir.v43i1.850 Bangladesh J. Sci. Ind. Res. 43(1), 97-102, 2008